2011
DOI: 10.1002/adfm.201100954
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Amphiphilic Janus Bubbles and Their Behavior at an Air–Water Interface

Abstract: This paper presents the generation of amphiphilic Janus bubbles and their behavior at an air–water interface. Janus bubbles are generated by selectively depositing gold onto one side of dried nanoparticle‐shelled bubbles. To generate nanoparticle‐shelled bubbles that can withstand drying without significant changes in their structure, it is critical to control the ratio of bubble radius to shell thickness using a microfluidic technique. It is observed that the behavior of Janus bubbles at an air–water interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
79
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 65 publications
3
79
0
Order By: Relevance
“…In the steady flow pattern, the average pressure and flow rate can be controlled. 24 . The images of the two flow patterns can be seen in Fig.…”
Section: Microfluidic Devicementioning
confidence: 95%
See 1 more Smart Citation
“…In the steady flow pattern, the average pressure and flow rate can be controlled. 24 . The images of the two flow patterns can be seen in Fig.…”
Section: Microfluidic Devicementioning
confidence: 95%
“…Upon evaporation of the organic solvent, the nanoparticles in the oil layer form a stiff shell at the air-water interface, which enhances the stability of the microbubbles against dissolution and coarsening. Teresa et al 24 also used the same device to prepare gas-in-oil-in-water double emulsions. Stride et al 25 reported a one-step approach to produce hollow microspheres with single holes in the shells by coaxial electrohydrodynamic atomization(CEHDA).…”
Section: Introductionmentioning
confidence: 97%
“…However, it was essential to match the generation rate and pitch of the droplets and the method often produced relatively thick shells. In contrast, Luo et al [28][29][30] and Lee et al [31][32][33] reported droplet formation methods using three-dimensional glass capillaries. They used a separated serial or simultaneous droplet generation structure to form core and shell layers.…”
Section: Introductionmentioning
confidence: 98%
“…Highly uniform microcapsules have been formed in miniaturized devices, and the functionality of these microcapsules has expanded as a result of new developments in microcapsule synthesis [22][23][24]. Formation of hollow microcapsules by direct injection of a gas into the capsule core is of particular interest [25][26][27][28][29][30][31][32][33][34]. Since the inner cavity and shell layer are formed directly in this technique, the number of materials available for capsule synthesis was significantly increased compared with single emulsion techniques using self-assembly or interfacial polymerization of the shell layer [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…We also assume that the Janus boundary does not cause undulation in the fluid interface, thus does not induce lateral capillary attractions between Janus dumbbells. [45][46][47][48][49] Results and Discussion…”
mentioning
confidence: 99%